The acute and long-term effects of olympic karate kata training on structural and functional changes in the body posture of polish national team athletes - Gawel, E.; Zwierzchowska, A. (Sports, 2024)
The aim of this study was to assess the acute and long-term effects of karate kata training on body posture (range of motion (ROM)) and musculoskeletal pain in elite karate athletes. Twelve kata athletes from the Polish national team participated in the study. A cross-sectional study protocol was used, with direct participatory observation (NMQ-7/6 questionnaire, spinal curvatures and spinal ROM testing, ROM of joints) and natural experiment (225 min of kata training) methods of assessment. Age and number of weekly kata sessions were found to correlate with ROM of the lumbar spine (R = (-0.6), p < 0.05). High increase in the prevalence of lumbar hypolordosis and posterior pelvic tilt was noted after karate training sessions. ROM of the inclination in the sagittal plane differed significantly between the first and second trials, by 10.0 degrees on average. Kata stances and their movement pattern seem to be related to the occurrence of disturbances in the ROM of the internal and external rotations of the hip joints and decreased depth of the lumbar lordosis, pelvic tilt, and their ROM. The locations of the long-term musculoskeletal complaints (NMQ-6) seem to result from compensatory changes that occur in the musculoskeletal structures as a result of elite-level kata training.